Plasmablasts Generated during Repeated Dengue Infection Are Virus Glycoprotein–Specific and Bind to Multiple Virus Serotypes - Xu, MeiHui; Hadinoto, Vey; Appanna, Ramapraba; Joensson, Klas; Toh, Ying Xiu; Balakrishnan, Thavamalar; Ong, Swee Hoe; Warter, Lucile; Leo, Yee Sin; Wang, Cheng-I; Fink, Katja (The Journal of immunology (1950), 2012)
Dengue virus immune protection is specific to the serotype encountered and is thought to persist throughout one’s lifetime. Many serotype cross-reactive memory B cells isolated from humans with previous dengue infection are specific for the nonstructural and the prM structural viral proteins, and they can enhance infection in vitro. However, plasmablasts circulating in enormous numbers during acute secondary infection have not been studied. In this study, we analyzed single plasmablasts from two patients by sorting the cells for Ig sequence analysis and for recombinant expression of Abs. In contrast to memory B cells, most plasmablast-derived Abs bound to the structural E protein of dengue, and protection experiments in mice revealed that virus serotypes encountered during past infections were neutralized more efficiently than were the serotypes of the current infection. Together with genetic analyses, we show evidence that plasmablasts in dengue patients are a polyclonal pool of activated E protein–specific memory B cells and that their specificity is not representative of the serum Abs secreted by long-lived plasma cells in the memory phase. These results contribute to the understanding of the phenomenon of original antigenic sin in dengue.